The prison is another country: incarcerated students and (im)mobility in Australian prisons. Issue 2 (4th May 2017) - Farley, Helen; Hopkins, Susan
ABSTRACT: Space, time and movement have particular meanings and significance for Australian prisoners attempting higher education while incarcerated. In a sense, the prison is another 'world' or 'country' with its own spatial and temporal arrangements and constraints for incarcerated university students. The contemporary digital university typically presupposes a level of mobility and access to mobile communication technologies which most Australian prisoners cannot access. This article examines the immobility of incarcerated students and their attempts to complete tertiary and pre-tertiary distance education courses without direct internet access. Drawing on critical mobilities theory, this article also explores attempts to address this digital disconnection of incarcerated students and where such interventions have been frustrated by movement issues within the prison. Prison focus group data suggest the use of modified digital learning technologies in prisons needs to be informed by a critical approach to the institutional processes and practices of this unique and challenging learning environment. This article also highlights the limitations and contradictions of painful immobilisation as a core strategy of Australia's modern, expanding penal state, which encourages rehabilitation through education, while effectively cutting prisoners off from the wider digital world.